Physical and physiological quality of soybean seeds at three speeds of the harvester - Carla S. S. Paixão; Camila P. Chrispin; Rouverson P. da Silva; Lucas A. S. Girio; Murilo A. Voltarelli (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The mechanized harvesting of soybean is a fundamental tool in the production process of this crop and, if not performed properly, it can result in severe mechanical damage to the seeds, causing significant losses at harvest, particularly due to reduced quality. Thus, this study aimed to evaluate the physical and physiological quality of soybean seeds at three speeds of the harvester, using statistical process control. The experiment was carried out in the municipality of Conceição das Alagoas, MG, Brazil, with three travel speeds: 4.5, 5.0 and 5.5 km h-1. The seed samples were collected at 20 min intervals for 3 h of operation, with a total of 9 samples for each speed. The evaluations were performed based on the following parameters: grain temperature, water content, concave opening, cylinder rotation, mechanical damage and electrical conductivity. The physical and physiological quality of the seeds was dependent on the displacement speed of machine. The highest speed led to lower mechanical damage and higher vigor of soybean seeds.